Adaptability and stability of grain yield in climbing and brown coat cowpea genotypes - Filho, Francisco Rodrigues Freire; Ribeiro, Valdenir Queiroz; Rocha, Maurisrael de Moura; Lopes, Ângela Celis de Almeida (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the adaptability and the grain yield stability of 16 cowpea (Vigna unguiculata (L.) Walp.) genotypes using the additive main effects and multiplicative interaction model. The trials were carried out at nine environments, locations and years, of the Middle-North region of Brazil, states of Piauí (PI) and Maranhão (MA), in the period from 1999 to 2001. Environments and genotype x environment interaction effects, and the first two axes of the analysis of principal component of the interaction were significant (P < 0.01). The analysis of principal components explained 61.25% of the sum of squares of the genotype x environment interaction. TE93-244-23F and TE93-210-12F-1 genotypes gathered genes for adaptability and stability, and can be cultivated in all environments. BR 17-Gurguéia, Canapuzinho and EPACE-10 genotypes presented the highest yield averages, but were unstable and with specific adaptation to environments of high quality. The environments more favorable were Bom Jesus, PI, 2000; Palmeira do Piauí, PI, 2001, and Sambaíba, MA, 2000. There was no tendency of locations grouping by State and the distribution was balanced in terms of environmental quality.